A resilient unwanted civil society: the gays and lesbians of Zimbabwe use of facebook as alternative public sphere in a dominant homophobic society - Mhiripiri, Nhamo A.; Moyo, Sithandazile B. (Palgrave Macmillan, Cham, 2021)
Queer gender and sexuality is largely condemned in the mainstream heterosexual Zimbabwean media and culture. Politicians have politicized queer identities and sexuality to win over what is perceived to be a homophobic majority. President Robert Mugabe is probably Africa’s most articulate and virulent critic of homosexuality and queer culture. The civil society organization Gays and Lesbians Association of Zimbabwe (GALZ) represents a social movement that has struggled to put its issues into the public sphere, at times winning cases in Zimbabwean courts of law. It is a social movement for lesbian, gays, bisexual, transgendered, transvestite and other so-called ‘queer’ sexuality and identities. This study focuses on how GALZ uses Facebook as an alternative platform of communication using online ethnographic interaction between defenders and critics of the LGTB community in Zimbabwe